Risk factors for respiratory symptoms in adults: The Busselton Health Study. Issue 5 (28th October 2013) - James, Alan L.; Knuiman, Matthew W.; Divitini, Mark L.; Hui, Jennie; Hunter, Michael L.; Mulrennan, Siobhain A.; Musk, A. W. 'Bill'
Abstract: Background and objective: The prevalence of reported doctor‐diagnosed 'asthma' increased between 1990 and 2005–2007 in Busselton, Western Australia, accompanied by increased reported cough and phlegm but not recent wheeze. Possible reasons for the increase in diagnosed asthma include environmental exposures and diagnostic transfer. The aim of this study was to relate subject characteristics and exposures to the presence of wheeze and/or current cough/phlegm in the 2005–2007 survey. Methods: A gender‐ and age‐stratified random sample of 2862 adults from the Busselton shire completed questionnaires regarding doctor‐diagnosed asthma, respiratory symptoms and environmental exposures; and measures of anthropometry, spirometry, exhaled nitric oxide (eNO), airway hyperresponsiveness (AHR) and atopy. Associations between respiratory symptoms and subject characteristics were assessed in 2656 subjects. Results: Wheeze was reported by 23% of subjects, cough/phlegm by 22% and both by 9%. The significant and independent correlates of wheeze were reflux symptoms, lung function, AHR, eNO, atopy, body mass index and smoking. The significant and independent correlates of cough/phlegm were reflux symptoms, lung function, smoking and dusty job. Subjects more likely to report only wheeze than only cough/phlegm were female, aged <40 years, atopic, had lower percentage predicted forced expiratory volume in one second (FEV1 ) or higher percentage predicted force vital capacity. Conclusions: A variety of risk factors was associated with wheeze or cough/phlegm or both. Increased non‐allergic exposures may account for increased prevalence of reported cough and phlegm and may contribute to increased reported asthma in adults. Abstract : This study analysed population data to determine the relationships between environmental exposures and respiratory symptoms that may contribute to reported wheeze or cough/phlegm in adults. It found that these symptoms have independent determinants and that diagnostic transfer may contribute to an observed increase in reported asthma in adults.